(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article presents modern approaches to the application of operations performed by traditional and laparoscopic methods for cholelithiasis. The possibilities of modern endovideosurgery for cholelithiasis are described in detail.